Impact of Hindiya Dam on the Limnological Features of Euphrates River to the North of Babil Governorate, Iraq (Baghdad Science Journal, 2022)
Five sites were chosen to the north of Babil Governorate in   order to identify the limnological features and the impact of the Hindiya Dam during 2019. Site2 was located near the dam to reflect the ecological features of this site, whereas other sites, S1 was located at the upstream of the dam as a control site. Moreover, the two other sites S3 and S4 were located down the dam. The results of  the  study  showed  a  close  correlation  between air and water temperature at all sites. Also there were significant differences in average of thirteen out of eighteen water parameters.Water temperature, total alkalinity, bicarbonate, DO, POS, TH and Mg+2  ions  decreased from 22.76˚C, 203.33 mg/L, 146.75 mg/L, 8.8 mg/L, 100.023%, 438 mg/L, 35.55mg/L, respectively on S2  to 22.66 ˚C, 200.28 mg/L, 145.58 mg/L, 8.35 mg/L, 95.45%, 422.66 mg/L,  28.81 mg/L, respectively at site below the dam. While, turbidity, TSS,  Ca+2,  SO2+4, NO3-2 and PO4-2 increased from 13.32 NTU, 23.08 mg/L, 116.89 mg/L, 107.5 mg/L, 1.027 mg/L and 0.019 mg/L, respectively on S2  to 26.574 NTU, 26.83 mg/L, 119.23 mg/L, 137.5 mg/L, 1.145 mg/L and 0.032 mg/L, respectively at the site below the dam.  However, no apparent dam effect was reported in EC, S, TDS, pH values at Euphrates River. No significant differences of all characteristics were found among sites except, turbidity, TSS, Mg+2,  SO+4 and PO4-2. It can be considered that the Euphrates River is very hard, oligohaline, slightly alkaline, well ventilated and clear to turbid. In addition, the turbidity and TSS values exceeded permissible limits of water quality for aquatic life in most samples especially in site below the dam. However, the river was considered by BOD5 to be doubtful in its cleanliness water. Calcium, magnesium, nitrate and phosphate values in this study were within permissible limits.